2020
DOI: 10.1016/j.ijfoodmicro.2020.108809
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extract assisted low-temperature pasteurization to inactivate enteric viruses in juices

Abstract: The current popularity of minimally processed foods is an opportunity for natural antimicrobial agents to be combined with mild heat treatments to act synergistically in reducing viral foodborne pathogens. Viral inactivation by heat-treatments (at 25, 40, 50 and 63 °C for 30 min) combined with aged green tea extract (aged-GTE) was initially evaluated in phosphate buffered saline (PBS) against murine norovirus (MNV-1) and hepatitis A virus (HAV) by cell culture, and against human norovirus by in situ capture RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
(19 reference statements)
3
6
0
Order By: Relevance
“…It was also found that the addition of aging GTE to mildly heat-treated juices increased the deactivation of MNV-1 by over 4 logs. The synergistic action of both antiviral agents reduced the infectivity of MNV-1, which confirms the hypothesis that GTE can be used as an additional control agent that improves food safety [ 99 ].…”
Section: Practical Application Of Metabolites Of Plant Origin In the Food Industrysupporting
confidence: 71%
See 2 more Smart Citations
“…It was also found that the addition of aging GTE to mildly heat-treated juices increased the deactivation of MNV-1 by over 4 logs. The synergistic action of both antiviral agents reduced the infectivity of MNV-1, which confirms the hypothesis that GTE can be used as an additional control agent that improves food safety [ 99 ].…”
Section: Practical Application Of Metabolites Of Plant Origin In the Food Industrysupporting
confidence: 71%
“…The antiviral activity of plant metabolites is the subject of many scientific studies [ 23 , 41 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ,…”
Section: Plant Preparations As Antiviral Agents Against Norovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…As there are no currently available disinfectants that can remove HuNoV inside the bivalve shellfish, it may be possible to consider investigating the application of TY-1 in this context. The results reported by Falco et al [ 52 ] suggested the possible synergistic virucidal activity of a gentle heat treatment with plant-derived components such as TY-1, which may contribute to controlling food-borne HuNoV transmission. Overall, further studies aiming to identify whether TY-1 can effectively inactivate HuNoV in bivalve shellfish foods, and on high-touch locations and food contact surfaces, are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the studies by Falcóa et al [ 100 ] used the HAV HM-175/18f strain (ATCC VR-1402) and FRhK-4 cells. GTE (Naturex SA, Avignon, France) was dissolved in PBS (pH 7.2) and incubated for 24 h (aged GTE) to increase antiviral activity.…”
Section: Review Of Antiviral Use Of Essential Oils Juices and Other Plant Extracts Against Havmentioning
confidence: 99%